Cumulative evidence for associations between genetic variants in interleukin 17 family gene and risk of human diseases - Liu, Tianyu; Yang, Lei; Lv, Xiaolong; Zuo, Chunjian; Jia, Chenhao; Yang, Zelin; Fan, Chongqi; Chen, Huanwen (Frontiers in Immunology, 2022)
Background Genetic association studies have elucidated the link of variants in the interleukin 17 (IL-17) family genes with susceptibility to human diseases, yet have obtained controversial outcomes. Therefore, we sought to update comprehensive synopsis of variants in the IL-17 family genes with susceptibility to human diseases. Methods Our study screened the Pubmed and Web of Science to enroll eligible articles and performed a meta-analysis, then graded the cumulative evidence of significant association using Venice criteria and false-positive report probability test, and finally assessed the function of variants with strong evidence. Results Seven variants in IL-17 family genes had significant relationships with susceptibility to 18 human diseases identified by meta-analyses. Strong evidence was assigned to 4 variants (IL-17A rs2275913, IL-17A rs8193037, IL-17F rs1889570, IL-17F rs763780) with susceptibility to 6 human diseases (lung and cervical cancer, spondyloarthritis, asthma, multiple sclerosis, rheumatoid arthritis), moderate to 2 variants with risk of 5 diseases, weak to 5 variants with risk of 10 diseases. Bioinformatics analysis suggested that the variants with strong evidence might fall in putative functional regions. Additionally, positive relationships for 5 variants with risk of 4 diseases (based on two datasets) and 14 variants with risk of 21 diseases (based on one dataset) were considered noteworthy. Conclusions This study offers updated and comprehensive clues that variants in the IL-17 family genes are significantly linked with susceptibility to cervical, lung cancer, asthma, multiple sclerosis, rheumatoid arthritis and spondyloarthritis, and elucidates the crucial role of the IL-17 regions in the genetic predisposition to cancer or noncancerous diseases.